2019
DOI: 10.2147/ndt.s237369
|View full text |Cite
|
Sign up to set email alerts
|

<p>Psychache and Suicidal History in Patients with Obsessive-Compulsive Disorder</p>

Abstract: Purpose: Suicide is an important cause of death in patients diagnosed with obsessivecompulsive disorder (OCD) as well as other psychiatric disorders. Early determining of risk factors provides an opportunity for intervention. The mediating effect of psychological pain (also known as psychache) on suicide has been shown in various disorders but has not been investigated in patients with OCD. In this study, we aimed to show the relationship between psychological pain and other clinical variables and suicide in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…A cross-sectional study by Demirkol et al (54) demonstrated that psychache might be positively associated with suicide attempts and occurrent suicidal thoughts, and alexithymia might be related to the negative symptom of schizophrenia and psychache in patients with a diagnosis of schizophrenia. Similarly, among the patients with obsessive-compulsive disorder (OCD), a strong correlation was found between psychache and previous suicide attempt (55). Psychache has also been shown to mediate the relationships between suicidal factors and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study by Demirkol et al (54) demonstrated that psychache might be positively associated with suicide attempts and occurrent suicidal thoughts, and alexithymia might be related to the negative symptom of schizophrenia and psychache in patients with a diagnosis of schizophrenia. Similarly, among the patients with obsessive-compulsive disorder (OCD), a strong correlation was found between psychache and previous suicide attempt (55). Psychache has also been shown to mediate the relationships between suicidal factors and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide will not occur without psychache. Relieving the psychache of patients with obsessive–compulsive disorder can decrease the intentions of suicide, even though comorbid depression is not diagnosed ( 7 ). External factors (e.g., family, school, and society) and internal factors (e.g., physiology and psychology) can influence psychache, and seeking social support can positively relieve psychache ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although basal ganglia injury may induce an abnormal behavior with obsessive−compulsive traits [15,16] in this patient the opposite was more likely: her repeated cleansing action resulted in toxic basal ganglia damage.…”
Section: Discussionmentioning
confidence: 99%